The insecure workforce (London, 2000)
"For the past two decades employment in Britain has been marked by a search for greater flexibility in the availability and use of labour. In recent years, however, there has been mounting concern at the costs of this trend and an appreciation that the consequence of a flexible labour market may be an insecure workforce, vulnerable to exploitation. It is also widely claimed that rising worker insecurity imposes costs on the wider economy and society through lower rates of skill formation, reduced consumer confidence and family instability.